Perancangan Game Tradisional Indonesia Panjat Pinang Berbasis Android Dengan Menggunakan Unity - Windarto, Yudi Eko; Prasetijo, Agung Budi; Luthfi, Naufal (STMIK Palangkaraya, 2019)
Nowadays, with the enourmous development of technology, it’s safe to say that Indonesian people are being too dependent on their electronic device or gadget. Many children now prefer to play with their gadget instead of playing traditional games outside with their friends. In Indonesia, there are many kinds of traditional games. For example, is Panjat Pinang. Panjat Pinang is a traditional game that Indonesian people usually played on the Commemorate of Independence Day of Indonesia. But, this traditional game usually can only be played by adults. The purpose of making this game is to provide a game that looks like Panjat Pinang that can be played by children and adults. This final project is made with the game concept that can run on Android smartphone. This application will be developed using Unity. With this game, Indonesian people still can get to know a kind of traditional game, Panjat Pinang.